Masculine migrations : reading the postcolonial male in "new Canadian" narratives - Coleman, Daniel, 1961- (Theory/culture series., 1998)
"This book examines the representation of masculinities in the fictions and autobiographies of some of Canada's most exciting writers, including Austin Clarke, Dany Laferriere, Neil Bissoondath, Michael Ondaatje, Ven Begamudre, and Rohinton Mistry, to show how cross-cultural migration disrupts assumed codes for masculine behaviour and practice. It is the first book-length study of masculinities in Canadian literature and also the first to discuss these prominent postcolonial writers in relation to one another."--Jacket